Extending boundaries of human resource concepts and practices: An innovative recruitment method for Indigenous Australians in remote regions - Pearson, Cecil; Daff, S. (Sage Publications Ltd., 2011)
Australian Indigenous people continue to experience low economic independence and acknowledged social dislocations believed to be underpinned by unattractive levels of participation in the labour market. Recent legal developments provide foundation for mining operators, the Australian governments, and Indigenous traditional owners to negotiate land-use agreements that feature commitment to deliver greater training and employment prospects for Aboriginal people. However, aspirations of Australian Indigenous people, who are deficient in written English expression, to obtain entry to new mainstream jobs are seriously curbed when confronted with recruitment processes requiring competencies in English reading and writing skills. In this paper is reported an assessment of an innovative recruitment process, devoid of the need to demonstrate English literacy skills, for Indigenous people seeking mainstream jobs in the mining sector. The relative features of the scheme are discussed in the context of a multinational mining company operating in northern Australia.